Pengembangan Alat Pendidikan Untuk Meningkatkan Minat Belajar Peserta Didik: Pengembangan Alat Pendidikan Untuk Meningkatkan Minat Belajar Peserta Didik - Samaloisa, Mira Santika; Mardiana, Ria; Syafithri, Selomita; Rahmanisa, Silvia (Jurnal Family Education, 2023)
Developing educational tools to increase students' interest in learning is something that is difficult to realize in the world of education. The aim of writing this article is to identify the role of educational tools in stimulating students' interest in learning and provide views on strategies for developing effective educational tools. In this context, educational tools include a variety of resources such as educational software, learning games, textbooks, and other interactive media. Students' learning interest is a key factor in a sustainable learning process and has an impact on academic achievement. The article writing method used involves literature analysis to evaluate the best approach in designing educational tools that motivate and attract students. The findings of this research indicate that attractive educational tools need to consider various factors, including the diversity of students' learning styles, active involvement, connection to the real world, as well as a playful and exploratory approach. The results of this research provide practical guidance for educators, curriculum developers, and educational tool designers to design educational products that are more effective in increasing students' interest in learning. By understanding the importance of motivating and engaging educational tools, it can be hoped that increasing interest in learning will encourage better academic achievement and create a more dynamic and satisfying learning environment for students.